A dynamic and spatially explicit modeling approach to identify the ecosystem service implications of complex urban systems interactions. (July 2019) - Pan, Haozhi; Zhang, Le; Cong, Cong; Deal, Brian; Wang, Yutao
Highlights: A 30 × 30 m coupled model of economics, land-use, and ecosystem services is constructed. A dynamic and spatially explicit ecosystem service index is developed. Reference scenario is compared to an ecosystem preservation district scenario. Ecosystem district policy is a critical tool for mitigating ecosystem impacts. Strategies for policy scenario analysis and stakeholder engagement is proposed. Abstract: A comprehensive understanding and modeling of socio-ecological systems can better assess how human-induced urban growth affects ecosystem service. This paper demonstrates a comprehensive socio-ecological system modeling approach to identify ecosystem service impacts that result from human activities within large, complex urban systems. It adds to the existing ecosystem impact assessment approaches by integrating spatiotemporal and socio-ecological process model with dynamic interaction and feedback between models and policies. The approach couples regional economics, urban land-use, and ecosystem interactions in a fine scaled (30 × 30 m) modeling framework with multiple time steps and feedback. The coupled model fuses a regional econometric input-output model with a dynamic land-use allocation model that spatially allocates the residential and commercial lands that are needed to satisfy the identified economic changes on an annual basis. A dynamic and spatially explicit index is constructed to measure the potential impacts of the economic/land use interactions on available ecosystem services. A scenario analysis is performed to test various ecologically oriented policy outcomes against noted ecosystem service impacts. The Chicago metropolitan region constitutes the study area with forecasts to 2040. Analysis results prove that models without inclusion of feedback dynamics and uncertainties could significantly under-estimate resulting ecosystem service impacts without. The scenario simulation shows a significant land-use developmental pattern restructure occurs when preservative policies are reinforced and significant ecosystem service loss reduction can also be achieved.